(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2020)
The enormous power of globalization influences not only the local communities but also the pattern of everyday life of the individuals who belong to those communities. The global often involves violence in its course to interact with the local. The Bauls of West Bengal (India) can be taken as a site where this process is salient. The ascetic-minstrel Bauls, the practitioners of Baul sadhona, who usually stick to their community and the silpi-artist Bauls who are not sadhoks but become globally famous Baul figures as singers and performers (of Baul song) can broadly be seen as local Bauls and global Bauls. The global pull-up tends to fracture, and so loosen, the unity of the Baul community based on certain crucial everyday activities as the new generations of Bauls in the post-independence era (of India) prefer more to be silpiartist Bauls than to be sadhok Bauls. It shows that the demarcation between the sadhok Bauls and silpi-artist Bauls, and local Bauls-global Bauls after them is flawed, for both in reality and in conception, they have always been in a state of flux. As these categories may re-position themselves on account of the changes occurred in real circumstances, so it is possible that the notions of “local” and “global” may flap. This phenomenon, as it may be termed “glocal”, is important in understanding the workings of global forces through which the global and local condition each other.